2021
DOI: 10.1136/bmjresp-2021-000998
|View full text |Cite
|
Sign up to set email alerts
|

Burden of cystic fibrosis in children <12 years of age prior to the introduction of CFTR modulator therapies

Abstract: BackgroundCystic fibrosis (CF) is a genetic, multisystemic, progressive and life-shortening disease caused by mutations in the CF transmembrane conductance regulator (CFTR) gene. Different genotypes have been linked to variations in disease progression among people with CF. The burden of illness (BOI) in children with CF is incompletely characterised, particularly as it relates to CFTR genotypes prior to the availability of the first CFTR modulators. This retrospective, cross-sectional, descriptive study evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
(53 reference statements)
0
2
1
Order By: Relevance
“…The observed PEx event rate was low (0.25/year) in this study and is lower than the rate reported for a large cohort of children of the same age range prior to initiating CFTR modulator therapy (0.4/year) [32] .…”
Section: Discussioncontrasting
confidence: 86%
“…The observed PEx event rate was low (0.25/year) in this study and is lower than the rate reported for a large cohort of children of the same age range prior to initiating CFTR modulator therapy (0.4/year) [32] .…”
Section: Discussioncontrasting
confidence: 86%
“…1,2 However, the clinical consequences of CF often appear in early childhood and require aggressive symptomatic treatment with the aim of preserving lung function and maintaining adequate nutrition and growth. 3 Unfortunately, some children still develop severe lung disease despite intensive care in specialized CF centers: the Italian CF Registry showed that about 1% of 674 children aged 6-11 years had <40% of predicted forced expiratory volume in the first second (FEV 1 ) in 2020 (personal communication). Such cases are extremely difficult to manage and, when conventional treatment fails, the only alternative is lung transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…As ETI becomes more widespread, longer-term natural history studies are warranted to determine impact on lung function, disease progression, and referral for lung transplant. Prior to the approval of CFTR modulators, CF has been associated with a high burden of illness in children [49 ▪ ], and modulators are increasingly used prior to the development of significant lung disease. Short-term studies of ETI in children aged 6–11 have demonstrated similar clinical improvements to adults [50 ▪ ] and an open-label study of children aged 2–5 years is in progress (NCT04537793).…”
Section: Discussionmentioning
confidence: 99%